2013
DOI: 10.1016/j.juro.2012.11.078
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Functional Outcome Following Radical Cystoprostatectomy and Ileal Neobladder Reconstruction in Male Patients

Abstract: Ileal orthotopic neobladder offers good functional results but most patients wear at least 1 pad and many require diapers at night. Increasing age and diabetes mellitus predict worse urinary function but are not associated with pad use. Emptying failure is uncommon and occurs early in the postoperative period. Pad size/wetness and mucus leakage should be considered when evaluating urinary incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 26 publications
3
45
1
Order By: Relevance
“…Of these 28 patients, 12 (43%) agreed to undergo multichannel UDS measurement. The mean preurodynamic PVR was 82 cm 3 (range 0-325 cm 3 ) was not independently associated with the overall BCI score ( Table 2). The presence of diabetes mellitus was independently associated with lower BCI scores.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Of these 28 patients, 12 (43%) agreed to undergo multichannel UDS measurement. The mean preurodynamic PVR was 82 cm 3 (range 0-325 cm 3 ) was not independently associated with the overall BCI score ( Table 2). The presence of diabetes mellitus was independently associated with lower BCI scores.…”
Section: Resultsmentioning
confidence: 94%
“…In addition, we did not have UDS or SF-36 results from the open ONB cohort for comparison, and baseline iONB characterization was not available because of the retrospective nature of the study. While the BCI is a validated instrument, the components added to tailor HRQOL assessment to orthotopic diversion E U R O P E A N U R O L O G Y X X X ( 2 0 1 5 ) X X X -X X X (questions on patterns of pad use and mucus), although published previously [3], are not validated. The above notwithstanding, our evaluation of iONB patients using functional data (not only pad number but also pad size, degree of wetness, and timing of incontinence) and a generic and a reliable bladder cancer-specific HRQOL instrument, and the benchmarking of results against open ONB are unique features of this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Ahmadi et al [14] reported continence rates on male patients who underwent radical cystectomy with neobladder as part of a clinical trial between 2002 and 2009 at the University of Southern California. Two hundred and sixty-three patients were mailed a survey at a minimum of 12 months after surgery, and 179 (68 % response rate) patients with a mean age of 70 years responded.…”
Section: Continencementioning
confidence: 99%
“…When bladder cancer is in question, the expectations of NS-RC appear even more attractive. In spite of the unquestionable improvement of patient's post-operative quality of life (QoL) related to the introduction of orthotopic bladder substitution (OBS), the frequent disturbances of the urinary continence (UC) [1,2] and the loss of the erectile function subsequent to conventional radical cysto-prostatectomy [3,4] may explain the Abstract Objectives To evaluate technical feasibility and oncologic and functional outcomes of three different surgical procedures of nerve-sparing radical cystectomy (NS-RC) for the treatment of organ-confined bladder cancer at a single referral centre. Materials and methods All consecutive cases of NS-RC carried out between 1997 and 2012 were retrospectively analysed.…”
Section: Introductionmentioning
confidence: 99%